Answer: 5.2 cm2
Step-by-step explanation:
Answer: 2 - 2*sin³(θ) - √1 -sin²(θ)
Step-by-step explanation: In the expression
cos(theta)*sin2(theta) − cos(theta)
sin (2θ) = 2 sin(θ)*cos(θ) ⇒ cos(θ)*2sin(θ)cos(θ) - cos(θ)
2cos²(θ)sin(θ) - cos(θ) if we use cos²(θ) = 1-sin²(θ)
2 [ (1 - sin²(θ))*sin(θ)] - cos(θ)
2 - 2sin²(θ)sin(θ) - cos(θ) ⇒ 2-2sin³(θ)-cos(θ) ; cos(θ) = √1 -sin²(θ)
2 - 2*sin³(θ) - √1 -sin²(θ)
Answer:
I believe the quiz had 18 questions, with a 14:4 ratio
The next term is double the previous term, so that the
-th term is given recursively by

This rule tells us that



and so on, with the explicit rule

for
.
If 512 is the
-th term in the sequence, then

2(x-3)=7x-31
2x-6=7x-31
-7x -7x
----------------
-5x-6=-31
+6 +6
--------------
-5x=-25
Divide by -5
x=5
3x-2(x+5)=-3+18
15
3x-2(x+5)=15
3x-2x-10=15
x-10=15
+10 +10
--------------
x=25